Insight into the development of silica-based materials as photocatalysts for CO2 photoconversion towards CH3OH : A review and recent progress - Mahadi, Bahari; Aishah, Abdul Jalil; Che Rozid, Mamat; Nurul Sahida, Hassan; Herma Dina, Setiabudi; Vo, Dai Viet N. (Elsevier B.V., 2022)
High exploitation of fossil fuel energy has resulted in substantial CO2 emissions into the atmosphere, leading to severe global warming. Tremendous strategies have been developed to explore possible approaches in minimizing the content of CO2 in the atmosphere. CO2 photoconversion into CH3OH has been put forward as a promising strategy since anthropogenic CO2 is utilized to generate valuable CH3OH assisting by clean solar energy. Silica-based materials have emerged as potential candidates for photocatalysts is accredited to their mesoporous framework with a large surface area, flexible tunability pore sizes, excellent thermal stability, and capability to suppress metal particle growth. Thus, this review encompasses the current progress on applying and developing silica-based materials as photocatalysts for CO2 photoconversion into CH3OH. Apart from that, fundamental aspects of the mechanism, the factors affecting performance, and the efficiency of silica-based materials in CO2 photoconversion to CH3OH are also comprehensively highlighted. The difficulties and prospects of CO2 photoconversion into CH3OH via silica-based materials are also discussed. In general, the most recent scenarios recommended further investigation to explore these materials since CO2 photoconversion to CH3OH has not been adequately investigated in the literature.